How to Avoid Mistakes in Software Development for Unmanned Vehicles - Szczepański, Cezary; Ciopcia, Marcin (Transactions on Maritime Science, 2019)
The purpose of this paper is to propose design and development methodology, in terms of robustness, of unmanned vehicles (UV) software development, which minimizes the risk of software failure in both experimental and final solutions. The most common dangers in UV software development were determined, classified and analysed, on the basis of literature studies, and the author's own experience in software development and in analysis of open-source code. As a conclusion, “good practices” and failure countermeasures were proposed.